(untitled) (Northern International Medical College Journal, 2017)
Background : The Thalassaemia is an inherited haemoglobulin disorder causes hemolytic anemia which usually requires life-long blood transfusion therapy. Therefore transfusion dependent thalassaemia major patients suffer from the effect of deposition of excess iron in the liver, heart and endocrine glands. Objective : The aim of present study was to find out the association of serum ferritin and SGPT in transfusion dependent thalassaemia major patient. Methodology : This cross sectional study was carried out in Day care unit (DCU) of Transfusion Medicine department, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during January 2014 to December 2014. Total of 110 clinically diagnosed Thalassaemia major (TM) between (5-35 years) cases of either sex from the above mentioned department attending the DCU were selected purposively for this study. Data were collected on clinical examination findings, laboratory investigations, ABO and Rh Blood Group, Serum ferritin and SGPT (Serum glutamic pyruvic transaminase) after taking informed consent. Results : The following observations and results were obtained in this study. The mean age was found 17.15±8.77 years with range from 5 to 35 years and male to female ratio was 1.2:1 (male 59 and female 51). Sixty eight (68.0%) patients came from rural area, 43.6% patients were student, 77.3% patients had completed primary education, 57.3% of the patients came from middle class family and 72.7% patients were unmarried. About 46.4% of the patients had moderate anaemia, 28.2% had jaundice, 79.1% had hepatomegaly, 82.7% had splenomegaly and 30.9% had complication due to iron overload. Mean haemoglobulin (Hb%) was found 6.65±1.63 gm/dl, mean serum ferritin was found 3785±17637 ?g/L and mean SGPT was found 134.8±77.94 U/L. There was a significant positive correlation (r=0.259; p=0.006) between serum ferritin and SGPT. Conclusion : Considering the study result it can be concluded that there is a positive significant correlation between serum ferritin with SGPT level. Northern International Medical College Journal Vol.8(1) July 2016: 170-173